Stowarzyszenie Młodzieży Polskiej w Szadku w latach 1919– 1933 - Stefańska, Dorota (Biuletyn Szadkowski, 2014)
Polish Youth Association in Szadek was set up in 1919 at the initiative of Jan Anglik. lt was then reorganized in the early 1920s by Father Edward Dyja and Dean Antoni Orzechowski. Afterwards it was successively run by Father Jan Stanisław Żak, Father Józef Gołębiowski and Father Jan Przybysz. It consisted of two sections: female youth and małe youth. The program of activity was defined by decrees of the secretariat of Włocławek diocese, headed by Father W. Zawadzki, Father A. Radomski, and next by Father S. Pietruszka. The association organized excursions and pilgrimages ( e.g. to Częstochowa and Charłupia Mała). In the field of cultural and educational activity, it organized vocational trainings, days of welfare work, youth rallies, and celebrations on the occasion of religious or national feasts. The aim of the association was formation of young generations of Poles in the spirit of patriotic and Christian values - the youth was involved in religious, social and cultural life of the parish under patronage of the clergy.